AKHLAK ISLAM DALAM INTERAKSI MEDIA SOSIAL: PANDUAN BERETIKA DI ERA DIGITAL - Fitranta, Aston (Majalah Ilmiah Tabuah: Ta`limat, Budaya, Agama dan Humaniora, 2025)
The rapid development of social media has introduced novel ethical challenges for Muslims interacting in digital spaces. This study aims to identify Islamic moral principles relevant to social media use, assess users’ compliance levels, and formulate a practical ethical guideline for the digital era. Employing a descriptive‑comparative literature review, the research examines the Quran (QS. Al‑Ḥujurāt [49]:6), Prophetic traditions, Indonesia’s 1945 Constitution Articles 28F & 28J(2), and prior studies. Findings reveal four core principles: information verification, ṣidq (truthfulness), ḥayā’ (modesty), and taʿāwun (mutual assistance). A three‑stage ethical model pre‑posting, during interaction, and post‑interaction is developed to curb the spread of hoaxes, slander, and hate speech. Theoretical implications enrich the Islamic digital ethics discourse by integrating maqāṣid al‑syarī‘ah with contemporary media theory, while practical implications yield an Islamic digital literacy module for educational and da‘wah institutions. Policy recommendations include crafting a collaborative “Islamic Digital Ethics Code” involving regulators, Islamic organizations, and social media platforms.